2021
DOI: 10.36655/sproket.v2i2.530
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Kecepatan, Temperatur dan Infill Terhadap Kualitas dan Kekasaran Kotak Relay Lampu Sign Sepedamotor Hasil dari 3D Printing

Abstract: 3D printing technology has great potential in today's manufacturing world where one of its uses is in the prototype of a product. One of the most famous and inexpensive 3D printing technologies is the Fused Deposition Modeling (FDM) method. Many studies have been carried out using this FDM method. In this study, the printing of motorbike light relay boxes was carried out using the FDM method with two variations of speed, temperature and infill of each mass. 3D Printing uses a nozzle diameter of 0.4 mm an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 2 publications
0
2
0
1
Order By: Relevance
“…G-Code making did to organize several parameters such as product position that will be printed on the 3D printer base layer using the layflat feature, support is functioning on holding the product part which is not getting surface contact with the base layer 3D printer, infill to set how solid the product will be printed, and adhesion that related to the foundation mediates the 3D printer base layer with the printed product. The 3D printed model uses PLA material and an FDM print machine [26]. Making 3D printing of heart organ is divisible into six parts: the aorta, right ventricle, left atrium, left ventricle, right atrium, and pulmonary artery.…”
Section: Diffusion Foundations and Materials Application Vol 33mentioning
confidence: 99%
“…G-Code making did to organize several parameters such as product position that will be printed on the 3D printer base layer using the layflat feature, support is functioning on holding the product part which is not getting surface contact with the base layer 3D printer, infill to set how solid the product will be printed, and adhesion that related to the foundation mediates the 3D printer base layer with the printed product. The 3D printed model uses PLA material and an FDM print machine [26]. Making 3D printing of heart organ is divisible into six parts: the aorta, right ventricle, left atrium, left ventricle, right atrium, and pulmonary artery.…”
Section: Diffusion Foundations and Materials Application Vol 33mentioning
confidence: 99%
“…Kecepatan pencetakan atau biasa disebut dengan print speed memengaruhi hasil pencetakan. Begitu juga dengan temperatur nozzle yang digunakan adalah 200° C. Kecepatan dan temperatur nozzle semakin tinggi akan memengaruhi kualitas produk [20]. Waktu proses pencetakan alat parallette dengan 3D printer untuk menentukan lama kerja dapat dikategorikan ke dalam tiga tahapan yaitu, (i) proses pencetakan 3D printer, (ii) assembly, dan (iii) finishing.…”
Section: Time Studyunclassified
“…From his research, it was concluded that all printing products have rough surface properties. From the influence of printing speed and nozzle temperature, the higher and lower percentage of infill produces better product quality and lower / smoother roughness [12].…”
Section: Introductionmentioning
confidence: 99%